Perancangan Automatic Placement Order Support Tools di PT X - Chelsy Sandrina Clarita Anen; I Gede Agus Widyadana (Jurnal Titra, 2021)
PT X is a global bicycle industry that develops, manufactures, and markets bicycles around the world. One of the brands produced by PT X is brand Y. The problem faced by the Supply Department of brand Y is the inaccuracy of scheduling and determining the number of the lot size of bicycle models in placing orders. This inaccuracy is due to a large number of models, model levels, and SKU (Stock Keeping Units) every year. The purpose of this research is to design placement orders as a supporting tool to predict the schedule and optimizing the number of order lot size in the long run. There are two methods that researcher used, which is qualitatively (by interview) and quantitatively (modeling based on data history and designing the system using Visual Basic Excel version 7.1). The result obtained by this research is the estimated order entered by the user in the system can be scheduled and optimized automatically using excel. The main conclusion that can be drawn is the design of placement orders as a supporting tool that can eliminate the inaccuracy planning of placing orders. This design has also been successfully verified and validated.